Endoscopic repair of traumatic sphenoid sinus meningoencephalocele with cerebrospinal fluid rhinorrhea: a case report and literature review - Tan, Jiarong; Zuo, Chengcheng; Guo, Feiying; Tang, Shunli (Frontiers in Surgery, 2025)
Traumatic sphenoid sinus meningoencephalocele with cerebrospinal fluid (CSF) rhinorrhea is a clinically rare condition, typically presenting as trauma-induced clear watery discharge from the nasal cavity and nasopharynx. Surgery is the mainstay of treatment, including open and endoscopic procedures. Herein, we report a case of traumatic sphenoid sinus encephalocele with CSF rhinorrhea that was successfully treated using an endoscopic transmaxillary posterior wall approach, and reviewed the literature on endoscopic approaches for this condition. Our clinical experience indicates that an endoscopic transmaxillary approach may be a novel and promising surgical option for this condition.